2015
DOI: 10.7554/elife.09017
|View full text |Cite
|
Sign up to set email alerts
|

An extrafollicular pathway for the generation of effector CD8+ T cells driven by the proinflammatory cytokine, IL-12

Abstract: The proinflammatory cytokine IL-12 drives the generation of terminally differentiated KLRG1+ effector CD8+ T cells. Using a Toxoplasma vaccination model, we delineate the sequence of events that naïve CD8+ T cells undergo to become terminal effectors and the differentiation steps controlled by IL-12. We demonstrate that direct IL-12 signaling on CD8+ T cells is essential for the induction of KLRG1 and IFN-γ, but the subsequent downregulation of CXCR3 is controlled by IL-12 indirectly through the actions of IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 62 publications
0
23
0
2
Order By: Relevance
“…In addition to the effects we described here: ie., suppression of innate IL-12 production by DCs, attenuation of effector differentiation into KLRG1+ effectors and the inhibition of IFNγ production by CD8 T cells, we have also observed decreased NK cell activation, decreased CD4 T cell responses and deficiencies in chemokine responsiveness of red pulp macrophages and monocytes following T. gondii vaccination of H. polygyrus infected mice (data not shown). The emerging consensus view from several publications, including our recent study of the CD8 effector differentiation during vaccination with T. gondii (12, 2022) indicates that the efficient generation of effector T cells occurs through a multi-step process that relies upon the optimal functioning of an interrelated network of innate antigen presenting cells, helper cells and accessory cells that provide costimulatory signals and cytokines. By each targeting multiple players in this integrated network, 1) helminth-induced Th2 responses and 2) regulatory mechanisms mediated by IL-10 (and perhaps TGFβ) may represent distinct pathways that may be individually sufficient to stall the development and dampen the function of effector T cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the effects we described here: ie., suppression of innate IL-12 production by DCs, attenuation of effector differentiation into KLRG1+ effectors and the inhibition of IFNγ production by CD8 T cells, we have also observed decreased NK cell activation, decreased CD4 T cell responses and deficiencies in chemokine responsiveness of red pulp macrophages and monocytes following T. gondii vaccination of H. polygyrus infected mice (data not shown). The emerging consensus view from several publications, including our recent study of the CD8 effector differentiation during vaccination with T. gondii (12, 2022) indicates that the efficient generation of effector T cells occurs through a multi-step process that relies upon the optimal functioning of an interrelated network of innate antigen presenting cells, helper cells and accessory cells that provide costimulatory signals and cytokines. By each targeting multiple players in this integrated network, 1) helminth-induced Th2 responses and 2) regulatory mechanisms mediated by IL-10 (and perhaps TGFβ) may represent distinct pathways that may be individually sufficient to stall the development and dampen the function of effector T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Spleen and peritoneal cell suspension were stained with the appropriate cell surface antibody and tetramer (PE-labelled SVLAFRRL-K b ) as previously detailed (12, 13). For intracellular staining, cells were restimulated ex vivo by plating 4–6 million cells with live T. gondii tachyzoites (MOI of 0.1) for 10–12 hr at 37C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, transition from CXCR3+KLRG1+ Tint cell to CXCR3-KLRG1+ Teff cell phenotype correlated with the loss of proliferation and terminal differentiation of effector cells. Interestingly, Yap and colleagues observed cycling T cells of CXCR3+KLRG1+ phenotype in an acute T. gondii vaccination model, and found that Teff cell terminal differentiation correlated with CXCR3 downregulation in an interleukin-12 and IFNγ dependent manner (Shah et al, 2015). Together with our results, these findings suggest that the precise timing of TCR and cytokine or chemokine signals may be important for regulating T cell amplification and effector differentiation during infection by modulating the number of CXCR3+KLRG1+ Tint cells.…”
Section: Discussionmentioning
confidence: 99%
“…In mice inoculated with T. gondii cysts , NK cell-derived IFN-γ promoted Ly6C hi monocyte maturation into F4/80 + macrophages and IL-12-producing Mo-DCs [154]. Recent work using a model of attenuated T. gondii tachyzoite vaccination reported that Ly6C hi monocytes in the extrafollicular splenic compartment secrete a late wave of IL-12 that promotes the formation of terminally differentiated (KLRG1 + ) T-gondii-specific effector CD8 + T cells [155]. …”
Section: Monocyte-mediated Defense Against Parasitesmentioning
confidence: 99%